PERANCANGAN SISTEM INFORMASI PENGELOLAAN DATA WARGA SEBAGAI IMPLEMENTASI KONSEP PAPERLESS DAN TRANSFORMASI DIGITAL - Dian Purnamasari; Henri Septanto (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
The concept of Paperless or reducing the use of paper and digital transformation is a form of utilizing environmentally friendly technology, this will have a wider impact when applied to an information system at the RT (neighborhood unit) level. This is what inspired the author to conduct a study entitled Design of Citizen Data Management Information Systems as the Implementation of the Paperless Concept and Digital Transformation. The data collection method is done through observation, interviews and references from secondary data, the system development model chosen by the author is the Software Development Life Cycle Waterfall. The citizen data management information system developed by this author is not only useful in assisting the management of citizen data at the RT level, especially because of time efficiency when compared to conventional systems which require residents to meet with the head of the RT. This information system will also have a positive impact on the environment because this information system applies the concept of paperless and digital transformation so that it is environmentally friendly.